Positive electrode slurry and preparation method thereof
Through the use of acrylics as a liquid agent in the lithium battery positive slurry, the problem of insufficient liquid battery pole chips is solved, and the battery's infiltration and circulation performance significantly improves the battery.
Patent Information
- Application Number
- CN202410260794.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2025-01-24
AI Technical Summary
The liquid retention performance of existing lithium battery electrodes is insufficient, resulting in difficulty in infiltration of the electrolyte of high-pressure lithium battery electrodes and poor circulation performance.
A liquid retaining agent composed of acrylic esters, specifically a combination of methacrylic acid and methyl methacrylate, is used as a liquid retaining agent in the positive electrode slurry to improve the wettability and liquid retention of the lithium battery pole pieces.
It significantly improves the viscosity, swelling rate, and electrolyte infiltration of the positive pulp, and enhance the capacity recovery rate and normal temperature cycle performance of lithium -ion batteries at high temperature storage conditions at 45 ° C.
Smart Images

Figure BDA0004730847460000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a positive electrode slurry and a preparation method thereof. Background Art
[0002] At present, with the increasing capacity of lithium batteries required by the market, the energy density of lithium batteries is constantly increasing, resulting in a corresponding increase in the surface density of the positive and negative electrodes of the lithium battery coating, and a greater compaction. However, it is difficult for the highly compacted lithium battery electrode to be infiltrated with electrolyte, and the amount of liquid retained in the electrode is reduced, resulting in poor cycle performance of the lithium battery. Therefore, it is necessary to improve the liquid retention performance of the lithium battery electrode.
[0003] There are two main methods for improving the liquid retention performance of existing lithium-ion batteries. One is to add a wetting agent to the electrolyte to improve the wettability of the electrolyte to the lithium battery pole piece, such as a positive electrode slurry composition, a positive electrode slurry, a positive electrode pole piece and a secondary battery disclosed in publication number CN114665092B. In this scheme, a synergist is added to the positive electrode slurry. The synergist is composed of a binder auxiliary agent, a wetting agent and a dispersant, and plays a synergistic role. The wetting agent is an amino alcohol compound, which solves the problem of poor wettability and easy cracking of the pole piece; the other is to add lithium carbonate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide and other compounds as a wetting agent to the lithium battery positive electrode slurry, and add an appropriate amount of positive electrode Wetting agents can improve the energy density of lithium batteries, improve the cycle life and stability of batteries, and reduce the self-discharge rate of batteries; however, the present invention finds that the above two methods have the following problems: when adding a wetting agent to the electrolyte, if the content of the added wetting agent is low, the wetting effect on the lithium battery pole piece is not significantly improved, and if the content of the added wetting agent is high, it will affect the initial effect and cycle performance of the lithium battery; adding NMP-insoluble compounds such as lithium carbonate and lithium cobalt oxide to the lithium battery positive electrode slurry will increase the dispersion of the positive electrode slurry and affect the processing performance of the lithium battery production process. Moreover, such compounds have a significant effect on reducing self-discharge, but have no obvious effect on improving the liquid retention performance of the lithium battery pole piece. Summary of the invention
[0004] The present invention provides a positive electrode slurry and a preparation method thereof. The positive electrode slurry comprises a liquid retaining agent composed of an acrylic acid ester substance. The positive electrode slurry contains a liquid retaining agent, which is an acrylic acid ester substance. The liquid retaining agent is composed of methacrylic acid and methyl methacrylate. The homogenization stability of the positive electrode slurry does not change significantly, the viscosity of the positive electrode slurry significantly decreases, the swelling rate of a film made of the positive electrode slurry and the electrolyte infiltration rising height significantly increase, the wettability and liquid retaining property of the positive electrode slurry are significantly improved, the storage battery capacity recovery rate of the lithium ion battery made of the positive electrode slurry under 45°C high-temperature storage conditions is improved, and the cycle performance of the battery under normal temperature cycle conditions is significantly improved.
[0005] The specific technical scheme of the present invention is: A positive electrode slurry comprises, by weight, 96.5 to 97.5 parts of active material, 1 to 1.5 parts of conductive agent, 1.5 to 2 parts of binder, 0.25 to 0.3 parts of liquid retaining agent and solvent; the liquid retaining agent is an acrylate substance, and the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.25 to 0.3:1.
[0006] Preferably, the liquid retaining agent comprises methacrylic acid and methyl methacrylate, and the mass ratio of methacrylic acid to methyl methacrylate is 7:3.
[0007] The invention provides a positive electrode slurry, which is composed of an active material, a conductive agent, an adhesive, a liquid retaining agent and a solvent. The liquid retaining performance of a film made from the positive electrode slurry is significantly improved, and the high-temperature cycle performance of a lithium-ion battery made from the positive electrode slurry is significantly improved; the liquid retaining agent in the positive electrode slurry is an acrylic acid substance, and the composition is composed of methacrylic acid and methyl methacrylate. The liquid retaining agent is added to the positive electrode slurry and can be dissolved in the solvent, and the viscosity of the positive electrode slurry is significantly reduced, and the dispersibility of the active material in the positive electrode slurry is not changed, thereby ensuring the homogenization stability of the positive electrode slurry; the liquid retaining capacity of the positive electrode slurry is significantly increased after the liquid retaining agent is added, and the film made from the positive electrode slurry is significantly increased in the infiltration and expansion height compared with the positive electrode slurry film without the liquid retaining agent added; the lithium battery made from the positive electrode slurry provided by the invention has no influence on the electrode sheet peeling force, full charge rebound and DCR of the battery, the storage battery capacity recovery rate of the battery under the high-temperature storage condition of 45°C is improved, and the cycle performance of the battery under the normal temperature cycle condition is significantly improved.
[0008] Preferably, the active material includes one or more of lithium iron phosphorus oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and composites thereof.
[0009] Preferably, the conductive agent includes one or more of conductive carbon black, conductive graphite, modified conductive graphite, metal particles, Ketjen black, acetylene black, carbon nanotubes, carbon fibers, graphene and conductive polymers.
[0010] Preferably, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer.
[0011] Preferably, the active material is lithium iron phosphate.
[0012] Preferably, the solvent is N-methylpyrrolidone.
[0013] A method for preparing the positive electrode slurry comprises the following steps: injecting active material, conductive agent, binder and liquid retaining agent into a homogenizing device and mixing them to obtain positive electrode slurry.
[0014] Preferably, the mixing conditions include: mixing at 600-650 r / min for 1-3 min and then mixing at 1000-1100 r / min for 10-12 min at 25°C.
[0015] Preferably, the viscosity of the positive electrode slurry is 4500-6500 mPa·s Compared with the prior art, the present invention has the following beneficial effects: (1) The positive electrode slurry provided by the present invention contains a liquid retaining agent, which is an acrylic substance, and the liquid retaining agent is composed of methacrylic acid and methyl methacrylate. The homogenization stability of the positive electrode slurry does not change significantly, the viscosity of the positive electrode slurry decreases significantly, the swelling rate of the film made of the positive electrode slurry and the electrolyte infiltration rising height increase significantly, and the wettability and liquid retention of the positive electrode slurry are significantly improved; (2) The electrode peeling force, full charge rebound and DCR of the lithium battery made of the positive electrode slurry provided by the present invention are not affected, the storage battery capacity recovery rate of the battery under high temperature storage conditions of 45°C is improved, and the cycle performance of the battery under normal temperature cycle conditions is significantly improved. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the embodiments.
[0017] Embodiment 1: A positive electrode slurry, comprising, by weight, 96.5 parts of an active material, 1.25 parts of a conductive agent, 1.5 parts of a binder, 0.3 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.3:1; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride, a liquid retaining agent and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 600 r / min for 1 min at 25°C, and then mixing at 1000 r / min for 10 min.
[0018] Embodiment 2: A positive electrode slurry comprises, by weight, 96.5 parts of an active material, 1.25 parts of a conductive agent, 1.5 parts of a binder, 0.3 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.3:1; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride, a liquid retaining agent and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 600 r / min for 1 min at 25°C, and then mixing at 1000 r / min for 10 min.
[0019] Embodiment 3: A positive electrode slurry, comprising, by weight, 96.5 parts of active material, 1.25 parts of conductive agent, 1.5 parts of binder, 0.3 parts of liquid retaining agent and solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.3:1 A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride, a liquid retaining agent and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 600 r / min for 1 min at 25°C, and then mixing at 1000 r / min for 10 min.
[0020] Embodiment 4: A positive electrode slurry, comprising, by weight, 97.5 parts of an active material, 1.5 parts of a conductive agent, 1.25 parts of a binder, 0.25 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.25:1; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride, a liquid retaining agent and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 650 r / min for 3 minutes at 25°C, and then mixing at 1100 r / min for 12 minutes.
[0021] Embodiment 5: A positive electrode slurry, comprising, by weight, 97.5 parts of an active material, 1.5 parts of a conductive agent, 1.25 parts of a binder, 0.25 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.25:1; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride, a liquid retaining agent and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 650 r / min for 3 minutes at 25°C, and then mixing at 1100 r / min for 12 minutes.
[0022] Comparative Example 1: (without adding liquid retaining agent) The difference between Comparative Example 1 and Example 1 is that: no liquid retaining agent is added in Comparative Example 1, and the other conditions are the same as those in Example 1; A positive electrode slurry, comprising, by weight, 96.5 parts of an active material, 1.25 parts of a conductive agent, 1.5 parts of a binder and a solvent, wherein the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 600-650r / min for 1-3min at 25°C, and then mixing at 1000-1100r / min for 10-12min.
[0023] Comparative Example 2: (The dosage of the liquid retaining agent is too low) The difference between Comparative Example 2 and Example 1 is that the mass ratio of the liquid retaining agent to the positive electrode slurry in Comparative Example 2 is 0.1:1, and the conditions are the same as those in Example 1; A positive electrode slurry, comprising, by weight, 96.5 parts of an active material, 1.25 parts of a conductive agent, 1.5 parts of a binder, 0.1 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 600-650r / min for 1-3min at 25°C, and then mixing at 1000-1100r / min for 10-12min.
[0024] Comparative Example 3: (The dosage of the liquid retaining agent is too high) The difference between Comparative Example 3 and Example 1 is that the mass ratio of the liquid retaining agent to the positive electrode slurry in Comparative Example 3 is 0.5:1, and the other conditions are the same as those in Example 1; A positive electrode slurry, comprising, by weight, 96.5 parts of an active material, 1 part of a conductive agent, 1.5 parts of a binder, 0.5 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 7 parts of methacrylic acid and 3 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; A method for preparing the above-mentioned positive electrode slurry comprises the following steps: lithium iron phosphate, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone are injected into a homogenizer according to the above-mentioned mass proportion and mixed to obtain a positive electrode slurry; the mixing conditions include: mixing at 600 r / min for 1 min at 25°C, and then mixing at 1000 r / min for 10 min.
[0025] Comparative Example 4: (the liquid retaining agent is only methyl methacrylate) The difference between Comparative Example 4 and Example 1 is that the liquid retaining agent in Comparative Example 4 is methacrylic acid, and the other conditions are the same as those in Example 1; A positive electrode slurry comprises, by weight, 96.5 parts of an active material, 1 part of a conductive agent, 1.5 parts of a binder, 0.3 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 10 parts of methacrylic acid, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; a method for preparing the above-mentioned positive electrode slurry comprises the following steps: injecting lithium iron phosphate, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone into a homogenizer according to the above-mentioned mass proportions and mixing to obtain the positive electrode slurry; the mixing conditions include: mixing at 600 r / min for 1 min at 25°C, and then mixing at 1000 r / min for 10 min.
[0026] Comparative Example 5: (the liquid retaining agent is only methyl methacrylate) The difference between Comparative Example 5 and Example 1 is that the liquid retaining agent in Comparative Example 5 is methyl methacrylate, and the other conditions are the same as those in Example 1; A positive electrode slurry comprises, by weight, 96.5 parts of an active material, 1 part of a conductive agent, 1.5 parts of a binder, 0.3 parts of a liquid retaining agent and a solvent, wherein the liquid retaining agent comprises, by weight, 10 parts of methyl methacrylate, the active material is lithium iron phosphate (LiFePO4), the conductive agent is conductive carbon black (SP), the binder is polyvinylidene fluoride (Arkema, HSV900), and the solvent is N-methylpyrrolidone; a method for preparing the above-mentioned positive electrode slurry comprises the following steps: injecting lithium iron phosphate, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone into a homogenizer according to the above-mentioned mass proportions and mixing to obtain the positive electrode slurry; the mixing conditions include: mixing at 600 r / min for 1 min at 25°C, and then mixing at 1000 r / min for 10 min.
[0027] Test example 1: The positive electrode slurries prepared in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3 are used to prepare positive electrode films and the liquid retention performance of the positive electrode films is tested, and the test items include swelling rate and wettability; The swelling rate test steps include: injecting the positive electrode slurry prepared in Examples 1 to 5 and Comparative Examples 1 to 3 into a mold, placing the film mold in an oven for baking to form a positive electrode film, taking the positive electrode film out of the mold and weighing it, the initial weight of the positive electrode film is recorded as M1, placing the film in an aluminum-plastic film filled with electrolyte at room temperature for 7 days and then taking it out, absorbing the electrolyte remaining on the surface of the film and weighing it, the weight of the positive electrode film after washing is recorded as M2, and calculating the swelling rate. The swelling rate calculation formula is (M2-M1) / M1×100%, and the test results are shown in Table 1; The wettability test steps include: injecting the positive electrode slurry prepared in Examples 1 to 5 and Comparative Examples 1 to 3 into a mold, placing the mold in an oven for baking to form a positive electrode film, vertically inserting the positive electrode film into an aluminum-plastic film filled with an electrolyte, the length of the positive electrode film immersed in the electrolyte is 1 cm, the immersion time is 7 days, and using a ruler to measure the rising height of the electrolyte on the positive electrode film after the electrolyte has been immersed in the film for 7 days. The test results are shown in Table 1; Table 1 Swelling ratio of positive electrode films of Examples 1 to 5 and Comparative Examples 1 to 3 Swelling rate (%) Electrolyte infiltration rise height (cm) Example 1 31.74 4.35 Example 2 31.95 4.33 Example 3 31.96 4.31 Example 4 21.78 3.03 Example 5 21.05 2.95 Comparative Example 1 14.46 2.71 Comparative Example 2 15.35 2.42 Comparative Example 3 15.86 3.34 Comparative Example 4 18.93 2.81 Comparative Example 5 18.31 2.63 As shown in the results of Table 1, the swelling rates of the positive electrode films of Examples 1 to 5 and Comparative Examples 1 to 3 show that the swelling rates of the positive electrode films of Examples 1 to 3 can reach 31%, the swelling rates of the positive electrode films of Examples 4 to 5 can reach 21%, and the swelling rate of the positive electrode film of Comparative Example 1 is 14%. The electrolyte infiltration rise heights of the positive electrode films of Examples 1 to 5 and Comparative Examples 1 to 3 show that the electrolyte infiltration rise heights of Examples 1 to 3 can reach 4.3 cm, the electrolyte infiltration rise heights of Examples 4 to 5 can reach 3 cm, and the electrolyte infiltration rise heights of Comparative Example 1 are 2.71cm; The swelling rate and electrolyte infiltration rise height of the positive electrode slurry film of Example 1 (adding a liquid retaining agent) are significantly higher than those of Comparative Example 1 (no liquid retaining agent is added). The results show that the positive electrode slurry of the present invention has a significantly improved ability to wet the electrolyte after adding a liquid retaining agent; In addition, through the results of the electrolyte infiltration rise height, it is found that the diffusion effect of the electrolyte in the film made of the positive electrode slurry is significantly enhanced, which can make the electrolyte diffuse evenly in the positive electrode slurry film and have a stronger adsorption and blocking effect on the electrolyte, which can significantly improve the liquid retention performance of the positive electrode slurry; From the results of Examples 1 to 5 and Comparative Examples 2 to 3, it is found that the amount of the liquid retaining agent has a great influence on the liquid retaining performance of the positive electrode slurry, and the amount of the liquid retaining agent can only have a promoting effect when it is between 0.25% and 0.3% of the positive electrode slurry; Compared with Comparative Example 1 (no liquid retaining agent added), Comparative Example 2 (the amount of the liquid retaining agent is too small) has an insignificant improvement in the swelling rate of the positive electrode slurry, and the infiltration rise height of the electrolyte decreases, which indicates that when the amount of the liquid retaining agent is too small, the wetting performance of the positive electrode slurry is not significantly improved and the liquid retention decreases; Compared with Comparative Example 1 (no liquid retaining agent is added), Comparative Example 3 (the amount of the liquid retaining agent is too large) has an insignificant improvement in the swelling rate of the positive electrode slurry, and the infiltration rise height of the electrolyte is not significantly improved. The results show that when the amount of the liquid retaining agent is too large, the wetting performance and liquid retention performance of the positive electrode slurry are not significantly improved, and instead decrease compared with the examples; It can be seen from the results of Example 1 and Comparative Examples 1, 4 and 5 that when only methacrylic acid is used as the liquid retaining agent in Comparative Example 4, the swelling rate of the positive electrode slurry film and the electrolyte infiltration rising height are not significantly improved. When only methyl methacrylate is used as the liquid retaining agent in Comparative Example 5, the swelling rate of the positive electrode slurry film is not significantly improved, and the electrolyte infiltration rising height is lower than that of Comparative Example 1. The above results show that when methacrylic acid or methyl methacrylate is used alone as the liquid retaining agent, the wetting performance and liquid retention performance of the positive electrode slurry are not significantly improved. Methacrylic acid and methyl methacrylate can produce a synergistic effect when used in combination, which can significantly improve the wettability and liquid retention of the positive electrode slurry.
[0028] Test example 2: The viscosity and homogenization stability of the positive electrode slurries prepared in the above Examples 1 to 5 and Comparative Examples 1 to 5 were tested. The test items included: slurry viscosity and homogenization stability. The slurry viscosity was tested using a viscometer, and the homogenization stability was filtered using a 150-mesh sieve. The test results are shown in Table 2. Table 2 Viscosity and slurry stability of positive electrode slurries of Examples 1 to 5 and Comparative Examples 1 to 5 Viscosity (%) Homogenate stability Example 1 4990 Sieve without filter residue Example 2 5055 Sieve without filter residue Example 3 5006 Sieve without filter residue Example 4 5220 Sieve without filter residue Example 5 5223 Sieve without filter residue Comparative Example 1 5800 Sieve without filter residue Comparative Example 2 6440 Sieve without filter residue Comparative Example 3 6350 Sieve without filter residue Comparative Example 4 5450 Sieve without filter residue Comparative Example 5 6455 Sieve without filter residue As shown in the results of Table 2, there is no residue after sieving through a 150-mesh sieve in Examples 1 to 5 and Comparative Examples 1 to 5. The results show that after adding methacrylic acid, methyl methacrylate and methacrylic acid / methyl methacrylate composition to the positive electrode slurry, the dispersibility of the positive electrode slurry is not affected, and the homogenization stability of the positive electrode slurry is high; Compared with Comparative Example 1 (without adding a liquid retaining agent), the viscosity of the positive electrode slurry of Examples 1 to 5 (adding a liquid retaining agent) is significantly reduced, while the viscosity of the positive electrode slurry of Comparative Example 2 (the amount of the liquid retaining agent is too small) and Comparative Example 3 (the amount of the liquid retaining agent is too large) is significantly increased compared with Comparative Example 1 and the embodiments. The results show that the amount of the liquid retaining agent affects the viscosity of the positive electrode slurry. In addition, it can be seen from the results of Comparative Examples 4 and 5 that the viscosity of Comparative Example 4 is significantly reduced compared with Comparative Example 1, while the viscosity of Comparative Example 5 is significantly increased compared with Comparative Example 1.
[0029] Test example 3: The positive electrode slurries prepared in Examples 1 to 5 and Comparative Example 1 were made into lithium-ion batteries, and the battery performance of the lithium batteries was tested. The test items included: pole piece peeling force, full charge rebound, DCR, 45°C high temperature storage cell capacity recovery performance and room temperature cycle; Lithium battery preparation steps: dissolve the binder and liquid retaining agent in NMP to form a glue solution, then add the conductive agent and the main material in turn, stir and disperse them completely to obtain a homogenous slurry, apply it on the foil, and then form a pole coil after rolling and slitting; punch, bake, stack, assemble, and weld the pole coil to the bare battery cell, and then fill the bare battery cell with liquid and package it; perform formation treatment on the battery cell, and obtain the formation data after it goes offline; The pole piece peeling force test steps include: taking three samples evenly (according to the example of 15mm width) on the rolled pole roll, sticking 3M tape on the steel plate carrier, sticking the pole roll sample on the 3M tape, and using a tensile tester to perform a 180° peeling force test to obtain peeling force data; The full-charge rebound test steps include: 1. Test the thickness of the electrode after baking, and record it as M1. 2. After formation, fully charge the battery cell and remove it from the production line, disassemble the battery cell in a constant humidity environment, take out the electrode and let it stand for 10 minutes, then test the thickness of the electrode, and record it as M2. 3. Electrode full-charge rebound rate = (M2-M1) ÷ M1 × 100%; The DCR test adopts the following method: take six square samples from the rolled pole coil through a sampler, use a pole piece impedance meter to test the internal resistance under a set pressure, record the DCR data and take the average value; 45℃ high temperature storage cell capacity recovery performance test steps: perform the first charge and discharge capacity test after the cell is offline, record it as the initial cell capacity, perform the charge and discharge capacity test after storing for a specific period (e.g. every 7 days) at 45℃, and record the data each time; The normal temperature cycle test steps include: charging rate is 1C, discharging rate is 1C, and cyclic charge and discharge test is performed at 25°C and rated voltage. The first discharge capacity is used as the initial capacity, and the capacity of each cycle is recorded and the capacity recovery rate is calculated. The test results are shown in Table 3; Table 3 shows the battery performance of the lithium batteries of Examples 1 to 5 and Comparative Example 1. As shown in Table 3, there is no significant difference in the electrode peeling force between Examples 1 to 5 (adding a liquid retaining agent) and Comparative Example 1 (no liquid retaining agent added), no significant difference in full-charge rebound performance, and no significant difference in DCR performance; after storage at a high temperature of 45°C, the cell capacity recovery rate of Examples 1 to 5 is better than that of Comparative Example 1. The results show that the cell capacity recovery performance of the lithium-ion battery after adding a liquid retaining agent after high-temperature storage at 45°C is improved, and the liquid retention performance of the electrolyte in the electrode is improved; In the room temperature cycle test (1C, 80%), the battery cycle performance of Examples 1 to 3 can reach more than 4500 cycles, the battery cycle performance of Examples 4 to 5 can reach more than 4300 cycles, and the battery cycle performance of Comparative Example 1 can only be more than 3200 cycles. The room temperature battery cycle performance of Examples 1 to 5 (adding a liquid retaining agent) is significantly higher than that of Comparative Example 1 (without adding a liquid retaining agent). The results show that the addition of a liquid retaining agent to the lithium battery of the present invention can significantly improve the room temperature cycle performance of the lithium battery.
[0030] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A positive electrode slurry, characterized in that: The invention comprises, by weight, 96.5 to 97.5 parts of active material, 1 to 1.5 parts of conductive agent, 1.5 to 2 parts of binder, 0.25 to 0.3 parts of liquid retaining agent and solvent; the liquid retaining agent is an acrylate substance, and the mass ratio of the liquid retaining agent to the positive electrode slurry is 0.25 to 0.3:
1.
2. A positive electrode slurry according to claim 1, characterized in that: The liquid retaining agent includes methacrylic acid and methyl methacrylate.
3. The positive electrode slurry according to claim 1, characterized in that: The active material includes one or more of lithium iron phosphorus oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and composites thereof.
4. The positive electrode slurry according to claim 1, characterized in that: The conductive agent includes one or more of conductive carbon black, conductive graphite, modified conductive graphite, metal particles, Ketjen black, acetylene black, carbon nanotubes, carbon fibers, graphene and conductive polymers.
5. The positive electrode slurry according to claim 1, characterized in that: The binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-propylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer.
6. A positive electrode slurry according to claim 1 or 3, characterized in that: The active material is lithium iron phosphate.
7. The positive electrode slurry according to claim 1, characterized in that: The solvent is N-methylpyrrolidone.
8. A method for preparing a positive electrode slurry according to any one of claims 1 to 7, characterized in that: The following steps are involved: Active material, conductive agent, binder and liquid retaining agent are injected into a homogenizing device and mixed to prepare positive electrode slurry.
9. The preparation method according to claim 8, characterized in that: The mixing conditions include: mixing at 600-650 r / min for 1-3 min and then mixing at 1000-1100 r / min for 10-12 min at 25°C.
10. The preparation method according to claim 8, characterized in that: The viscosity of the positive electrode slurry is 4500-6500 mPa·s.
Citation Information
Patent Citations
A positive electrode slurry composition, a positive electrode slurry, a positive electrode sheet, and a secondary battery thereof.
CN114665092B